Generalized Plasticity - Yu, Mao-Hong.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
Generalized Plasticity deals with the plasticity of materials and structures. It is an expansion of the "Unified Strength Theory to Plasticity Theory", leading to a unified treatment of metal plasticity and plasticity of geomaterials, generally. It includes the metal plasticity for Tresca materials, Huber-von-Mises materials and twin-shear materials and the geomaterial plasticity for Mohr-Coulomb materials, generalized twin-shear materials and the Unified Strength Theory. The book is divided into five major parts: 1. Yield function and choice; 2. Constitutive relation; 3. Slip-line Field Theory for plane strain problems, Characteristics Field Theory for plane stress problems and Characteristics Field Theory for spatial axisymmetrical problems; 4. Plastic zone analysis at crack tip and fracture criterion for mixed mode crack; 5. Limit loads and shakedown loads for pressure vessel. Examples of applications and problems are given for most chapters.
Stress Space and Stress State -- Basic Characteristics of Yield of Materials under Complex Stress -- Unified Strength Theory and Its Material Parameters -- Reasonable Choice of a Yield Function -- Elasto-plastic Constitutive Relations -- Concrete Plasticity -- Twin-Shear Slip-Line Field for Plane Strain Problem -- Unified Slip-Line Field Theory for Plane Strain Problem -- Twin-Shear Characteristics Field for Plane Stress Problem -- Unified Characteristics Field Theory for Plane Stress Problem -- Unified Characteristics Line Theory for Spatial Axisymmetric Problem -- Unified Solution of Plastic Zones at Crack Tip under Small Scale Yielding -- Unified Fracture Criter ion for Mixed Mode Crack Initiation and Fatigue Crack Growth -- Limit Load and Shakedown Load of Pressure Vessel.
Keywords: Mechanics; Mechanics, Applied; Structural materials; Solid Mechanics; Solid Mechanics; Structural Materials